(10+6):4 +3 ×[ 7+2×(25:5-1)-42:(5+1)+2]-5×4
Răspunsuri la întrebare
Răspuns de
1
(10+6):4 +3 ×[ 7+2×(25:5-1)-42:(5+1)+2]-5×4
=
= 16 : 4+3* [ 7+2×(5-1)- 42: 6+2]-20= 4+ 3*( 7+8 -7+2) -20=
= 4+3*10-20= 34-20=14
= 16 : 4+3* [ 7+2×(5-1)- 42: 6+2]-20= 4+ 3*( 7+8 -7+2) -20=
= 4+3*10-20= 34-20=14
Alte întrebări interesante
Informatică,
9 ani în urmă
Matematică,
9 ani în urmă
Istorie,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă